Innovative management of Oral Submucous Fibrosis (0SMF): Synergistic effects of photobiomodulation, antioxidants and mouth opening exercises – A case report - Gupta, Muskan; Shashikumar, Pratibha (Hasanuddin University, 2024)
Objective- Oral submucous fibrosis (OSMF) is a chronic and gradually progressing condition characterized by progressive fibrosis and restricted oral mucosal elasticity. It is prevalent in certain regions of the world, particularly South Asia, and is strongly linked to the habitual use of areca nut and tobacco. The present case report explores the combined therapeutic potential of antioxidants and photobiomodulation (PBM) in managing OSMF along with mouth opening exercises.Methods- A 31-year-old male patient presented with burning sensations in the cheeks with restricted mouth opening. The treatment protocol consisted of six sittings of PBM therapy at three-day intervals, coupled with antioxidant supplementation for 2 months, and mouth opening exercise.Result- The patient showed significant improvement in symptoms, with a marked increase in mouth opening from 3.0 cm to 3.5 cm.Conclusion- This case highlights the synergistic benefits of PBM and antioxidants along with mouth opening exercises as a promising non-surgical treatment for OSMF.Key words- Oral submucous fibrosis, reactive oxygen species, antioxidants, photo biomodulation